2016
DOI: 10.1002/cppb.20031
|View full text |Cite
|
Sign up to set email alerts
|

Telomere‐Mediated Chromosomal Truncation for Generating Engineered Minichromosomes in Maize

Abstract: Minichromosomes have been generated in maize using telomere‐mediated truncation. Telomere DNA, because of its repetitive nature, can be difficult to manipulate. The protocols in this unit describe two methods for generating the telomere DNA required for the initiation of telomere‐mediated truncation. The resulting DNA can then be used with truncation cassettes for introduction into maize via transformation. © 2016 by John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…The typical size range of a centromere satellite unit is 120 to 180 base pairs (bp), which is approximately the length of DNA required to encircle a nucleosome that provides the initial level of DNA packaging within chromatin. For example, the length of a monomer DNA satellite is 178 bp in Arabidopsis thaliana, 177 bp in radish ( Raphanus sativus ), and 156 bp in maize . However, satellite DNA repeat units as short as 20 bp have been found in Astragalus sinicus and as long as 5390 bp in potatoes .…”
Section: Plant Artificial Centromeresmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical size range of a centromere satellite unit is 120 to 180 base pairs (bp), which is approximately the length of DNA required to encircle a nucleosome that provides the initial level of DNA packaging within chromatin. For example, the length of a monomer DNA satellite is 178 bp in Arabidopsis thaliana, 177 bp in radish ( Raphanus sativus ), and 156 bp in maize . However, satellite DNA repeat units as short as 20 bp have been found in Astragalus sinicus and as long as 5390 bp in potatoes .…”
Section: Plant Artificial Centromeresmentioning
confidence: 99%
“…For example, the length of a monomer DNA satellite is 178 bp in Arabidopsis thaliana, 13 177 bp in radish (Raphanus sativus), 14 and 156 bp in maize. 15 However, satellite DNA repeat units as short as 20 bp have been found in Astragalus sinicus 16 and as long as 5390 bp in potatoes. 17 Until now, the technical constraints in amplification and cloning processes make it challenging to obtain large tandem DNA repeats directly from plant genomes.…”
Section: ■ Plant Artificial Centromeresmentioning
confidence: 99%
“…Moreover, the TMCT was faithfully transmitted to the next generation, and truncated chromosome can recombine with normal chromosome via Cre/lox or FLP/FRT recombination system, indicating the successful application of the TMCT platform ( Yu et al, 2007 ; Xu et al, 2012 ). Diverse length of Arabidopsis-type telomere repeat TTTAGGG were inserted into maize ( Yu et al, 2006 , 2007 ; Gaeta et al, 2011 ; Swyers et al, 2016 ), rice ( Oryza sativa ; Xu et al, 2012 ; Xu and Yu, 2016 ), Arabidopsis ( Nelson et al, 2011 ; Teo et al, 2011 ), barley ( Hordeum vulgare ; Kapusi et al, 2012 ), wheat ( Triticum aestivum ; Yuan et al, 2017 ), and Brassica napus ( Yan et al, 2017 ; Yin et al, 2021 ) by agrobacterium-mediated transformation or biotransformation, and TMCT were generated, which revealed that minichromosomes could be created in most of plant species by TMCT approach.…”
Section: Plant Artificial Chromosomesmentioning
confidence: 99%
“…It contains 2.5 kb of Arabidopsis telomere sequence. Using the cloning protocol described (Swyers et al 2016), 2 kb of telomere sequence was placed into WY9PZPNOS 1.4, just inside of the Right Border sequence. Stbl 4 cells were used to stabilize the telomere repeat.…”
Section: Construct Designmentioning
confidence: 99%
“…Appendix 2 describes cloning of telomere DNA into a construct in detail. Positive transformants were screened using a colony hybridization and Southern Blot analysis (Swyers et al 2016) (Figure 6).…”
Section: Construct Designmentioning
confidence: 99%